2006
DOI: 10.1080/01421590600877889
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pilot careers advice service for junior doctors

Abstract: This study evaluates a pilot careers service for junior doctors provided by a non-medical careers adviser. Evaluation forms and interviews indicate high satisfaction with this service. The junior doctors valued help with CVs and interviews, information regarding career routes and meetings with senior doctors arranged by the adviser. A longitudinal survey suggests that these doctors became clearer about their career pathways compared with controls, although they did not view the adviser as influencing their car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
1
7
0
2
Order By: Relevance
“…5 Results of our study appear to confirm the importance of residency preparation activities among graduating medical students ( Table 2).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…5 Results of our study appear to confirm the importance of residency preparation activities among graduating medical students ( Table 2).…”
Section: Discussionsupporting
confidence: 89%
“…4 Some studies have evaluated specific components of medical career-counseling programs and found that only certain activities were valued by students. 5,6 A Danish study noted the importance of having knowledge of what each specialty entails, that is, the facts about working conditions and specialty characteristics. 7 Another study supports this notion and reports that individual aspects of each specialty (e.g., lifestyle, salary expectations) are important in trying to determine what influences specialty choice.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is clearly stated in the MMC guidelines that those who provide career advice need to be appropriately trained 3. Unbiased opinions are needed and impartial trained career advisors have been shown to be more successful 34 35. Following the publication of the document Career management: an approach for medical schools, deaneries, royal colleges and trusts in 2005,3 deaneries have a structure for educational supervisors to access expert career advice.…”
Section: Putting It Into Paediatric Practicementioning
confidence: 99%
“…É também relevante para os sistemas de saúde e seus gestores 2 , uma vez que o equilíbrio entre a oferta de especialistas das diferentes áreas e as demandas da população por cada uma delas é fator crucial para a organização adequada da assistência à saúde 3,4,5 .…”
Section: Introductionunclassified
“…Há, ainda, interconectando ambas as esferas, a problemá-tica dos médicos que abandonam o treinamento na especialidade por se verem frustrados ou inseguros com a carreira que escolheram 1,3,7 , apontando a possível consequência do preparo insuficiente para a tomada dessa decisão 2 . Essa situação repercute negativamente na dinâmica dos serviços de saúde e nos programas de residência médica 8 .…”
unclassified